Matrix vesicle biogenesis in vitro by rachitic and normal rat chondrocytes. - Anderson, H. C. (1990)
Calcifying matrix vesicles (MVs) are released from chondrocytes and osteoblasts in monolayer culture. In the present studies, we tested the ability of rachitic versus normal rat growth plate chondrocytes in micromass or monolayer primary cultures to produce MVs. Unlike earlier reports of in vitro MV biogenesis by chicken chondrocytes in which most MVs were released into the medium, we found that most of the released rat matrix vesicles were entrapped in a newly formed cartilaginous matrix enveloping the cells. These matrix-associated MVs could be isolated by mild collagenase treatment and concentrated by differential centrifugation. Vesicle production slowed in the older 2- to 4-week-old cultures and, unlike vesicle release from cultured chicken chondrocytes, active vesicle production did not show a second burst of activity at 3 to 4 weeks. Alkaline phosphatase (ALP) activity diminished with time in culture in cells and matrix vesicles, suggesting a decrease in differentiative expression. Protein profiles on SDS polyacrylamide gels of native matrix vesicles and culture-derived MVs from rachitic and normal cells were quite similar and showed a typical simplified protein pattern as compared to chondrocyte plasma membrane proteins. There were distinctive proteins migrating at 130, 80 to 95, 66, 43, 20, and 14 kd. Culture-derived MVs showed vigorous in vitro calcifying activity that was ALP related. We conclude that 1) rachitic chondrocytes are essentially normal in their matrix vesicle production; 2) matrix entrapment of MVs is a characteristic of rat chondrocyte cultures; and 3) culture-produced MVs are similar to native MVs in protein profile and calcifiability, and thus can be studied as a model for normal MV composition and calcification.